2022
DOI: 10.3390/land11060945
|View full text |Cite
|
Sign up to set email alerts
|

Boon or Bane? Urban Food Security and Online Food Purchasing during the COVID-19 Epidemic in Nanjing, China

Abstract: This paper examines the relationship between the rapid growth of online food purchasing and household food security during the first wave of the COVID-19 pandemic in China using the city of Nanjing as a case study. The paper presents the results of an online survey of 968 households in Nanjing in March 2020 focused on their food purchasing behavior and levels of food security during the early weeks of the pandemic. While online food purchasing has increased rapidly in many countries during the COVID-19 pandemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…In 2015, the United Nations announced 17 Sustainable Development Goals (SDGs) covering social, economic, and environmental aspects promoting healthy and secure lives and making cities safe and sustainable by 2030 [32]. In recent years, e-commerce and OFS have undergone sustained but uneven growth worldwide [33]. While SDG 2 (Zero hunger) is a major goal, in the wake of the COVID-19 pandemic, people experienced less economic access to food because of income loss and hikes in food prices due to sudden shortages, and ultimately, it was difficult to maintain food security [34].…”
Section: Role Of Ofs In Global Agendamentioning
confidence: 99%
“…In 2015, the United Nations announced 17 Sustainable Development Goals (SDGs) covering social, economic, and environmental aspects promoting healthy and secure lives and making cities safe and sustainable by 2030 [32]. In recent years, e-commerce and OFS have undergone sustained but uneven growth worldwide [33]. While SDG 2 (Zero hunger) is a major goal, in the wake of the COVID-19 pandemic, people experienced less economic access to food because of income loss and hikes in food prices due to sudden shortages, and ultimately, it was difficult to maintain food security [34].…”
Section: Role Of Ofs In Global Agendamentioning
confidence: 99%
“…It has a 30-day recall period and includes nine questions about psychological and behavioral factors influencing food security at the household level [49,70]. These questions ask about people's feelings of uncertainty or anxiety related to food supply, as well as the preferability, variety, and quantity of foods consumed at the household level [82]. While the HFIAS was initially developed for program monitoring and impact evaluation, it has been used in other circumstances as well [49].…”
Section: Household Food Insecurity Access Scale and Household Hunger ...mentioning
confidence: 99%
“…Research addressed purchase intention, convenience, satisfaction, trust, and other factors of online community purchases [13,14]. Liang et al [15] showed that, during the COVID-19 pandemic, the online food purchases of urban residents became an important distribution format. Global retail e-commerce sales reached USD5.2 trillion in 2021, and are forecast to grow by 56%, reaching USD8.1 trillion by 2026 [16].…”
Section: Introductionmentioning
confidence: 99%